Market Intermediation, Publicness, and Securities Class Actions - Hillary A. Sale; Robert B. Thompson (Washington University Law Review, 2015)
Securities class actions play a crucial, if contested, role in the policing of securities fraud and the protection of securities markets. The theoretical understanding of these private enforcement claims needs to evolve to encompass the broader set of goals that underlie the securities regulatory impulse and the publicness of those goals. Further, a clear grasp of the modern securities class action also requires an updated understanding of how the role of market intermediation in securities transactions has reshaped the realities of securities litigation in public companies and the evolution of the fraud cause of action in the context of open-market transactions. The Supreme Court’s embrace of market efficiency as a mechanism to establish reliance in its 1988 decision, Basic Inc. v. Levinson, illustrates the necessary adaptation of common-law fraud to the modern market setting, and congressional enactment of the PSLRA in 1995 exemplifies the efforts to respond to the litigation risks inherent in that adaptation. Together, Basic and the PSLRA provide a framework for understanding both a series of recent Supreme Court decisions on securities class actions and a different understanding of the theory undergirding those class actions. To develop this understanding, we expand the conversation about the goals of securities regulation to include the set of goals that are rooted in publicness and focus on market protection, innovation, and growth, as well as stability and systemic considerations. We posit that this broader theoretical understanding explains why the Court rejected a challenge to the fraud-on-the-market doctrine and, instead, permitted the continued use of market efficiency: the Court chose to preserve the deterrence and enforcement role of these cases in promoting market growth and innovation. We then apply this understanding of publicness and market intermediation to the interpretation of the Court’s limited, but ambiguous, use of “price impact” in securities-fraud cases. Our analysis reveals that the practical balance established by Basic and the PSLRA has prevailed over pure doctrinal approaches to issues like reliance or other, more incomplete, theoretical explanations focused solely on compensation, deterrence, and investor protection, but neglects the role of publicness in the securities markets.
Keywords: Publicness; Securities Law; Corporate Law; Securities class action; Market intermediation; Fraud-on-the-market doctrine; Securities fraud